Political Event as The Unrepresentable Dimension in Art - Žukauskaitė, Audronė (Religija ir kultūra, 2012)
This article reconsiders the interface between politics and aesthetics in Jacques Rancière’s work. Rancière claims that the unrepresentability in art in some specific cases is commensurate with the unthinkability of a political event. Rancière finds the paradigmatic example of such commensurability in Claude Lanzmann’s film Shoah (1985). The discourse of the unrepresentable originates from the Kantian notion of the sublime and the subsequent modifications of this notion in Jean-François Lyotard’s philosophy. Lyotard displaces the sublime in the field of modern art, defining it as the art of negative presentation. This negativity refers both to the unrepresentable dimension in modern art and the unthinkable dimension of traumatic political events, such as the Holocaust. Contrary to this strategy of sublime adoration, Giorgio Agamben and Georges Didi-Huberman argue against the unrepresentable and claim the necessity “to stare at the unsayable”. For example, Didi-Huberman in his Images In Spite of All provocatively rejects the formal choices of Lanzmann’s Shoah and insists on the necessity to make or present images “in spite of all”. In my article, I want to build on this controversy by introducing into it Michael Haneke’s film The White Ribbon (2009), which plays on both sides: on the one hand, it uses the negative aesthetics of the sublime, very similar to that of Lanzmann’s film, and on the other hand, it examines violence present at the core of our everyday life.